Dynamic traffic grooming in IP/MPLS over WDM networks - Chen, Bin (2008)
IP/MPLS over WDM network is a promising candidate for the next generation optical Internet network. To efficiently operate such a network, traffic grooming is important in inter-working between the WDM network that supplies bandwidth at the wavelength granularity, and the attached client networks, e.g. the IP/MPLS network, that usually require connections of sub-wavelength granularity. Among the interconnection models between the IP/MPLS layer and the optical layer, the overlay model is seen as the most practical model for near-term deployment. In this work, we focus on investigating and proposing novel and practical dynamic traffic grooming policies in IP/MPLS over WDM mesh networks under the overlay model.